Une autre tasse de thé? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Le gouvernement ougandais a établi un Office du thé pour remplacer l’Uganda Tea Authority (UTA) et l’ Uganda Tea Growers Corporation (UTGC), ces deux structures n’étant pas parvenues